Елена Шварц. «Мыслей свитый шар»: лекции о метафизической школе ленинградской поэзии - Little (Hrsg.), Laura (Wiener Slawistischer Almanach, 2024)
In fall 2007, Saint Petersburg poet Elena Shvarts (1948–2010) held a series of lectures about Leningrad underground poetry between 1960 and 1980 at the University of Wisconsin (USA). This publication presents transcripts of three of her lectures, in which Shvarts introduces Viktor Krivulin, Alexander Mironov, and herself through discussion of several poetic works. As it documents a rare instance of the poet commenting extensively on her own poems, found in the third and fourth lectures, this publication will be of particular interest to readers and scholars of her work.